2003
DOI: 10.1007/s00256-003-0715-0
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative myositis in a patient with AIDS

Abstract: We report a case of proliferative myositis in the right biceps of a 56-year-old man with acquired immune deficiency syndrome (AIDS). Imaging methods included sonography, computed tomography and magnetic resonance imaging. The diagnosis was made by a core-cut biopsy and fine needle aspiration biopsy with immunohistochemical analysis. The lesion disappeared after 2 months without treatment. It is particularly important to determine whether intramuscular masses arising in patients with AIDS are due to an infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…10,16 Other imaging modalities, preferably magnetic resonance imaging (MRI), may need to be performed. Although PM in this study appears as isointense comparing to the surrounding muscle on T1-weighted (T1w) image, 3,9,10,14,16,23,30 hypointense lesions have also been previously reported. 36,37 PM also appears as a hyperintense mass 9,10,12,14,16,28,29 with variable hypointense linear structures 12,16,25 on T2-weighted (T2w) image.…”
Section: Imagingmentioning
confidence: 43%
See 3 more Smart Citations
“…10,16 Other imaging modalities, preferably magnetic resonance imaging (MRI), may need to be performed. Although PM in this study appears as isointense comparing to the surrounding muscle on T1-weighted (T1w) image, 3,9,10,14,16,23,30 hypointense lesions have also been previously reported. 36,37 PM also appears as a hyperintense mass 9,10,12,14,16,28,29 with variable hypointense linear structures 12,16,25 on T2-weighted (T2w) image.…”
Section: Imagingmentioning
confidence: 43%
“…This "stripe sign" is not specific for PM and can be found in other soft tissue tumors such as myositis ossificans and granular cell tumor. 38 Upon contrast injection, the lesion usually reveals homogenous enhancement 9,12 but heterogenous enhancement can also be seen. 3,4 Positron emission tomography (PET) was also performed in some previous studies and revealed PM as a "hot spot".…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although proliferative myositis grows rapidly, it is actually a benign lesion and can regress or completely resolve spontaneously. The incidence of proliferative myositis remains unknown, however recurrence is extremely rare (2). Although the cause of proliferative myositis remains unclear, a history of recent local trauma may be a risk factor, as noted in some reports (1,3,4).…”
Section: Introductionmentioning
confidence: 99%